Studi Potensi Daya Pembangkit Listrik Tenaga Mikrohidro (PLTMH) di Kampung Ubadari Kabupaten Fakfak - Yulianto La Elo; Rusliadi Rusliadi; Muhammadon Mokan; Febriyan Febriyan (Universitas Darul Ulum, 2023)
Fakfak Regency, West Papua Province has several rivers and waterfalls that have the potential to produce electrical energy. One of the areas in Fakfak Regency that has abundant water resource potential is Kayuni District, Fakfak Regency. So far, the use of this river and waterfall has been as a water source for villagers in Kayuni District and as one of the main tourist destinations in Fakfak Regency. Through this research, it is hoped that this resource can be developed for other potentials, one of which is for Micro Hydro Power Plants (PLTMH). Research is carried out by conducting surveys and direct measurements where the results of the measurements will be calculated to determine the potential for river flow discharge and potential for electricity generation. The results of measurements and calculations showed that the average flow of the Ubadari river was 4,674 m3/second, the effective fall height (Heff) of the flow was 4 m. With these results, it is estimated that the electrical power produced will be 111,402 kW.